The Relationship of Higher Education and Lifelong Learning Regarding the Labour Market’s Expectations - Kucsma, Daniella; Kőmíves, Péter Miklós (Acta Scientiarum Socialium, 2015)
The Relationship of Higher Education and Lifelong Learning Regarding the Labour Market’s Expectations.The aim of this article is to identify and clarify those needs of the labour market which are relevant for the higher education and for the conception of the lifelong learning. First of all, we expounded the expectations of the labour market concerning the national budgetary support of the higher educational system. We focused on the opinion of the Hungarian European Business Council (HEBC) and after examining their official statement, we checked all the statistical data shared by the HEBC. We also analysed the available statistical data of lifelong learning. Based on our analyses, we made a special model experiment to calculate how much more an employee can earn in Hungary if she or he has at least a bachelor degree. Our hypothesis was that the employees with higher education qualification can earn more than employees without a degree. After checking the calculations the findings evidenced that our hypothesis is correct.The publication was supported by the SROP-4.2.2.B-15/1/KONV-2015-0001 project. The project has been supported by the European Union, co-financed by the European Social Fund.
Keywords: higher education economics; lifelong learning; returns on investment in education